Cholesterol-conjugated polyethylenimine 25K for safe gene delivery into human carcinoma cells - Wanlop Weecharangsan, Boon-ek Yingyongnarongkul, Praneet Opanasopit (Journal of Applied Pharmaceutical Science, 2022)
Low cytotoxicity is a major requirement of a safe gene delivery vehicle. In this study, cholesterol-conjugated polyethylenimine 25K (PEI25K-CL) was used to evaluate the buffer capacity, the complexing ability with plasmid DNA, pEGFP, colloidal properties, pEGFP expression and transfection efficiency, and cytotoxicity in HeLa cervical carcinoma cells. The buffer capacity of PEI25K-CL was close to that of PEI25K. The PEI25K-CL/pEGFP and PEI25K/pEGFP complexes were completely retained at the polymer/DNA ratios of above 0.5:1. The particle size of PEI25K-CL/pEGFP complexes was 220 ± 7 to 402 ± 34 nm, depending on the polymer/DNA ratio. The pEGFP expression and transfection efficiency of the PEI25K-CL/pEGFP complexes were higher than those of pEGFP and lower than those of the PEI25K/pEGFP and LipofectamineTM2000/pEGFP complexes. The cytotoxicity of the PEI25K-CL/pEGFP complexes was significantly lower than that of the PEI25K/pEGFP complexes. This study concluded that PEI25K-CL could be an efficient and safe gene delivery vehicle.
Keywords: Polyethylenimine, cholesterol, gene delivery, plasmid DNA, cytotoxicity